2011
DOI: 10.1186/1471-2458-11-918
|View full text |Cite
|
Sign up to set email alerts
|

Drinking behaviours and blood alcohol concentration in four European drinking environments: a cross-sectional study

Abstract: BackgroundReducing harm in drinking environments is a growing priority for European alcohol policy yet few studies have explored nightlife drinking behaviours. This study examines alcohol consumption and blood alcohol concentration (BAC) in drinking environments in four European cities.MethodsA short questionnaire was implemented among 838 drinkers aged 16-35 in drinking environments in four European cities, in the Netherlands, Slovenia, Spain and the UK. Questions included self-reported alcohol use before int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 43 publications
4
54
1
1
Order By: Relevance
“…Our findings reinforce the importance of responsible service of alcohol within the nightlife, as the intention to consume more alcohol in these areas can be addressed with appropriate implementation and enforcement of such policies in licensed venues, which is in line with findings from the community-based interventions in California and Stockholm (Holder et al, 2000;Wallin et al, 2005;Wallin et al, 2003), and with recommendations by Bellis et al (2010). Most importantly, and in line with ------IJADR 6(1) ------recommendations by Hughes et al (2011), interventions that have been successful at reducing population-level consumption of alcohol, such as increased price and restricted/reduced trading hours, should be implemented, given these would likely be most effective at increasing safety in the nightlife context.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings reinforce the importance of responsible service of alcohol within the nightlife, as the intention to consume more alcohol in these areas can be addressed with appropriate implementation and enforcement of such policies in licensed venues, which is in line with findings from the community-based interventions in California and Stockholm (Holder et al, 2000;Wallin et al, 2005;Wallin et al, 2003), and with recommendations by Bellis et al (2010). Most importantly, and in line with ------IJADR 6(1) ------recommendations by Hughes et al (2011), interventions that have been successful at reducing population-level consumption of alcohol, such as increased price and restricted/reduced trading hours, should be implemented, given these would likely be most effective at increasing safety in the nightlife context.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Bellis et al (2010) reported that 79% of their 214 U.K. nightlife patrons intended to consume more alcohol, and 51% of those who already described themselves as drunk intended to consume more alcohol throughout the night. Hughes et al (2011) found that males across four European cities intended to consume more alcohol over the rest of the night than females, and 11% of their 838-participant sample reported having used, or intended to use, illicit drugs. Further, Reed et al (2011) found that U.S. participants interviewed entering bars later in the evening intended to get drunker than those entering earlier.…”
Section: Introductionmentioning
confidence: 99%
“…The study took place in four European cities: Liverpool, U.K.; Ljubljana, Slovenia; Palma de Mallorca, Spain; and Utrecht, the Netherlands (for further information on each city, see Hughes et al, 2011a). Sixty venues were identified for inclusion in the study, 15 within each study site.…”
Section: Methodsmentioning
confidence: 99%
“…The training included a test bar observation, with research coordinators completing the schedule (and incident forms if necessary) independently after the visit and comparing and discussing ratings at a meeting the following day. The training program was then repeated by research coordinators, in their respective countries, with recruited field researchers (see Hughes et al, 2011a;.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation